2018
DOI: 10.3390/w10060781
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalizing Participation in Water Resource Development: Bottom-Up and Top-Down Practices in Southern Thailand

Abstract: Substantive stakeholder engagement is increasingly recognized as essential for effective water resource development. Infrastructure development projects and strategies are however typically designed by engineers first before initiating discussions about impacts with stakeholders. In altering this sequence, designing meaningful participatory planning processes needs careful attention. This requires an innovative approach taking into account the institutional and discursive structure of the negotiation arena. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Effective and sustainable water management depended on stakeholders participating in decisions linked to water development. Singto et al [18] concluded that "participation should be institutionalized and facilitated in a way that fosters accountable representation by all stakeholders, builds trust, and'recognizes stakeholder interests and knowledge".…”
Section: Target 6b-stakeholder Participationmentioning
confidence: 99%
“…Effective and sustainable water management depended on stakeholders participating in decisions linked to water development. Singto et al [18] concluded that "participation should be institutionalized and facilitated in a way that fosters accountable representation by all stakeholders, builds trust, and'recognizes stakeholder interests and knowledge".…”
Section: Target 6b-stakeholder Participationmentioning
confidence: 99%
“…Based on the information gathered from onsite data collection, various calculation and assessment of water relation and its correlation to the wastage of the revenue have been divided into the following calculations [19,20,34]: i…”
Section: Methods To Assess the Data By Top-down Approachmentioning
confidence: 99%
“…The average daily consumption was derived by using annual consumption data, number of population, and total water consumption over the year. The average daily per capita consumption of IoT, Ambo University was derived using the following jargons [34,35]:…”
Section: Water Consumption In the Iot Campusmentioning
confidence: 99%
“…Outcomes for stakeholders further depend on how they are included in the decision-making process, e.g. whether they are only informed, or consulted and have had the chance to codesign interventions and make decisions (Singto et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In conflicts, affected stakeholders often claim that participatory tools are biased and limit their engagement in the dam planning process (Singto et al 2018). Elicitation methods and discussions with affected people need to systematically improve to engage affected stakeholders (Van Asselt and Rijkens-Klomp 2002).…”
Section: Introductionmentioning
confidence: 99%